The effect of a novel spark-plug plasma synthetic jet actuator on the performance of a PEM fuel cell. (September 2019) - Seyhan, Mehmet; Akansu, Yahya Erkan
Highlights: Effect of a novel spark-plug plasma synthetic jet on PEM fuel cell is investigated. Present study provides a new insight into PEM fuel cell. PEMFC shows 11% increase in the peak power output as compared to SPSJ actuator off. SPSJ actuator is enhanced the oxygen concentration and diffusion rate. Abstract: The effect of oscillating flow on the performance of a single cell PEM fuel cell is investigated at the cathode side. The oscillating flow is generated with a Spark-plug plasma synthetic jet (SPSJ) actuator. The PEM fuel cell is directly connected to SPSJ actuator. The significant performance improvement of the PEM fuel cell is by this approach. At two different hydrogen and air flow rates, necessary experiments are performed to obtain the polarization curves and current–time history plots at a constant voltage. The results indicate that the peak power output of the PEMFC increases up to 11% compared to the case without a SPSJ actuator. It can be concluded that the plasma synthetic jet actuator producing oscillating flow enhances the oxygen concentration and diffusion rate at the cathode channel of the PEM fuel cell.